Analysis Of Meaning Of Hero Hanabi`S Qoutes In Mobile Legend Game - Syah, Viki Mahdian; Rullyanti, Merry; Putra, Dhanu Ario (Literary Criticism, 2025)
Sociology and language are closely related. Sociolinguistics studies speakers and listeners of languages through the study of various aspects. In this bond between social and language, the application taken is sociolinguistic in qoutes. qouts are quotes that are used within a certain range. Based on this research, it is known that researchers discovered different types of qoutes. qouts are not only special words that exist in the sphere of society, but also found in online games. In this study, Mobile Legend Online Game was the object of analysis selected by the researchers. Data collection and analysis completion using a type of qualitative descriptive research. The result of this research is a sociolinguistic analysis of what heo hanabi qoutes mean in Mobile Legend Online Games, using data reduction techniques, data display, and conclusion verification. The data taken is also based on quotes spoken by Hanabi heroes. researchers have found 15 quotes that have denotative meanings and 35 quotes which have conotative meaning in Mobile Legend Online Games and researchers found 37 factors that influence entering into the motivational factor and 13 factors that affect entering in the environmental factor. Then the most dominating meaning in qoutes is connotative meaning and the most influencing factor is the motivational factor.With the results of this research, the researchers hope that this research can be significant data for the linguistic community and can also be a source of data, reference data, and comparison for future researchers, especially research on sociolinguistics. Based on this research, it is expected that the results can add insight to readers about the meaning of qoutes in various game situations and how it is pronounced by the hero in the Mobile Legend Online Game.